Formalization of characteristics of interaction of vehicles and pedestrians in conflict areas in the crossroad territory - Соколова, Наталя Олександрівна (Eastern-European Journal of Enterprise Technologies, 2014)
Based on the analysis of statistics of road traffic accidents in Ukraine at unregulated crossroads, the task on improving the methods for assessing the safety of unregulated crossroads taking into account qualitative accident rate indicators that characterize the severity of road traffic accidents was set in the paper. According to the analysis of the interaction between vehicles and pedestrians, the concepts of conflict area of interaction between traffic and pedestrian flows in the crossroad territory were introduced. Five specific interaction areas were identified. For the corresponding conflict areas in the crossroad territory, formalization of the specified interaction between vehicles and pedestrians at the level of the characteristics of the interaction process in time within the day was held. It was proposed to reflect the interaction using the law of conservation of energy. In this regard, energy characteristics of interaction between vehicles and pedestrians in the corresponding conflict areas were synthesized by the proposed five types of interaction between traffic and pedestrian flows.